Digital Minimalism: On Living Better with Less Technology - Cal Newport (Penguin Business, 2019)
The urge to pick up our phones every few minutes has become a nervous twitch that shatters our time into shards too small to be present. Our addiction to tech leaves us feeling exhausted and overwhelmed. But it doesn't have to be that way. In this timely book, professor Cal Newport shows us how to pair back digital distractions and live better with less technology. Introducing us to digital minimalists -- the calm, happy people who can hold long conversations without furtive glances at their phones or obsessively document everything they eat -- Newport reveals how to live more intentionally in our tech-saturated world. By following a thirty-day 'digital declutter' process, you'll learn to: · Rethink your relationship with social media · Prioritize 'high bandwidth' conversations over low quality text chains · Rediscover the pleasures of the offline world Take back control from your devices and become a digital minimalist.